The phenomenon of magnetic vortices superconducting for (Sr2RuO4) - Hussein Ali Mohammed (Tikrit Journal of Pure Science)
The study of superconducting vortices have been describes by a series of magnetometry experiments conducted on unconventional superconductors which is Sr2RuO4, using Scanning Hall probe microscopy technique (SHPM) (Tc ≈ 1.5 K). In this study have numerous samples as well propose that the vortex behaviour is modiﬁed with little amounts of disorder. Experimentally the better chips show a clear ﬁeld driven triangular to square vortex lattice transition at low ﬁelds, as predicted by extended London theory calculations. In stark disparity, somewhat less well-ordered chips exhibit pronounced vortex chaining banding that which tentatively attribute to an extrinsic source of disorder.